Right ventricular functional changes detected by CMR during ajmaline challenge in patients with Brugada syndrome. (25th November 2020) - Tondi, L; Mecarocci, V; Sturla, F; Pica, S; Giannelli, L; Ciconte, G; Camporeale, A; Santinelli, V; Lombardi, M; Pappone, C
Abstract: Background: 3D echocardiography has recently revealed alterations of right ventricular (RV) function in Brugada syndrome (BrS) during ajmaline challenge (AC). Cardiac magnetic resonance (CMR) is the gold standard for functional and anatomical RV assessment. CMR feature-tracking (FT) analysis is able to detect subtle functional changes in the underlying myocardial substrate. Purpose: To investigate RV functional changes during AC in BrS patients using CMR-FT analysis. Methods: 24 consecutive BrS and 28 matched controls underwent CMR. CMR protocol included paraxial and parasagittal cine bSSFP sequences, acquired before and 2÷5 minutes after ajmaline infusion (1 mg/kg in 5 minutes), to obtain a comprehensive evaluation of the RV free wall. All patients were closely monitored with ECG. Semi-automatic threshold-based quantification of ventricular volumes, function and mass was performed in QMass. CMR-FT analysis of RV function was performed in QStrain. Values of longitudinal strain (LS) and transverse displacement (TD) of the RV wall before and after AC were compared in BrS patients and in the control group. Results: AC induced Type 1 ECG pattern in all BrS patients and no ECG changes in controls. In BrS patients TD of the RV free wall was significantly reduced (P≤0.003) at peak ajmaline effect; controls reported sub-millimetric TD changes. LS of the RV wall was significantly impaired in BrS patients (P<0.0001) on both b SSFP sequences; LS remained comparable (P=0.62) in controls on the parasagittal sequence; minor but not negligible (P=0.01) LS changes were noticed on the paraxial stack. (Table 1) Conclusions: In patients with BrS CMR-FT analysis during AC unveils dysfunctional RV wall mechanics in areas generally associated with abnormal electrical activity. Funding Acknowledgement: Type of funding source: None